Relationship between cycling speed and blood lactate level at various intervals following 1-km time trial cycling - Gupta, S.; Stanula, A.; Goswami, A.; Adhikari, A.; Singh, A.; Ostrowski, A. (Journal of Kinesiology and Exercise Sciences, 2022)
Background: The aims of this study were (1) to assess the relationship between cycling speed and blood lactate ([BLa]) at various intervals following 1-km Time Trial cycling (1-kmTT) and (2) to determine the arrival time of peak blood lactate ([BLa]peak) during recovery. Methods and results: In 12 track cyclists, [BLa] was determined at 3 min ([BLa]3min), 5 min ([BLa]5min), and 7 min ([BLa]7min) of the recovery period following 1-kmTT. The highest [BLa] among the 3 recovery blood samples was recorded as the [BLa]peak. Heart rate was recorded during the race. Correlation (r) and effect size (ES) between average cycling speed and [BLa] were determined. Results: [BLa]3min (18.15±2.80 mmol/L) was the highest, followed by [BLa]5min (17.32±2.65 mmol/L) and [BLa]7 min (15.80±2.58 mmol/L), whereas [BLa]peak was 18.23 ± 2.78 mmol/L. Peak heart (HRpeak) (189.4±4.2 beats/min) of the cyclists attained during 1-kmTT was 97.8±1% of their maximal heart rate. Average cycling speed (14.31 ± 0.53 m/s) showed best correlation with [BLa]peak (r=0.582, p=0.047, ES=LARGE), followed by [BLa]3min (r=0.561; p=0.058, ES=LARGE), [BLa]5min (r=0.48; p=0.114, ES=MEDIUM) and [BLa]7min (r=0.382; p=0.221, ES=MEDIUM). Conclusion: In conclusion, (1) 1-kmTT performance is best correlated with [BLa]peak, and (2) usually [BLa]peak arrives 3 min following the race.